Shear behaviour of geopolymer concrete beams without stirrups. (1st September 2017) - Visintin, P.; Mohamed Ali, M.S.; Albitar, M.; Lucas, W.
Highlights: Shear capacity of geopolymer concrete beams investigated. Shear friction behaviour of geopolymer concrete determined experimentally. Segmental and FIB approaches able to adequately predict shear failure load. Abstract: The environmental impact of Ordinary Portland Cement (OPC) production has driven substantial interest in the development of new types of 'green' concrete, one of which is geopolymer concrete. If geopolymer concretes are to be widely used in practice, either existing design methodologies must be shown to be applicable or new design methodologies must be developed. To address this need, in this paper a recently developed mechanics based segmental approach for predicting the shear capacity of reinforced concrete (RC) beams is extended and applied to reinforced geopolymer concrete beams without stirrups. The results of eight reinforced geopolymer concrete beam tests without stirrups are presented along with the results of four direct shear tests with low levels of confinement. Significantly, the results of the direct shear tests show that the shear-friction properties for the geopolymer concrete utilised in the experimental investigation fall within the range of shear-friction properties of established OPC concrete. Moreover, it is shown that the segmental approach proposed can predict the shear capacity of geopolymer concrete beams with good accuracy and hence can be used as a tool to aid in the development of new design guidelines for geopolymer concrete.